2000
DOI: 10.1038/modpathol.3880207
|View full text |Cite
|
Sign up to set email alerts
|

CD44H and CD44V6 Expression in Different Subtypes of Hodgkin Lymphoma

Abstract: CD44 is a broadly distributed family of cell surface glycoproteins. The expression of CD44H has been documented in both Hodgkin lymphoma and nonHodgkin lymphoma. CD44V6 has been associated with more aggressive behavior in non-Hodgkin lymphoma, but such a correlation has not been established in Hodgkin lymphoma. In addition, the utility of CD44 and CD44V6 in the subclassification of Hodgkin lymphoma in paraffin-embedded tissues has not previously been evaluated. The current study included formalin-or methacarn-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A receptor for MIF is CD74, 32 the expression of which was reported on HRS cells. 33 CD44, another protein identified in our study, has been reported to be expressed in HL 34,35 and is involved in MIF-CD74 receptor complex by providing the required signaling component. 36 The MIF-CD74 receptor complex activates mitogen activated protein kinase signaling pathways and results in induction of several target genes important in inflammation and proliferation.…”
Section: Discussionmentioning
confidence: 62%
“…A receptor for MIF is CD74, 32 the expression of which was reported on HRS cells. 33 CD44, another protein identified in our study, has been reported to be expressed in HL 34,35 and is involved in MIF-CD74 receptor complex by providing the required signaling component. 36 The MIF-CD74 receptor complex activates mitogen activated protein kinase signaling pathways and results in induction of several target genes important in inflammation and proliferation.…”
Section: Discussionmentioning
confidence: 62%
“…The 20 transcripts with the highest decrease or increase in expression are shown in Tables 1 and 2. Several genes previously reported to be specifically expressed or upregulated in HRS cells were found to be upregulated in this study also, namely the actin-bundling protein Fascin (18 tags in L1236:0 tags in GC B cells), the chemokine TARC (14:0), TNF (8:1), CD44 (6:0), neuron-specific enolase 2 (8:1), and CCR7 (18:0) whereas a few other genes, such as IL-13 and CD30, were not identified (2,3,19,21,22,(28)(29)(30). The latter could be due to a relatively low level of gene expression or the presence of gene polymorphisms in the tag sequences of L1236, which is known to be positive for both CD30 and IL-13 (19,22).…”
Section: Generation and Comparison Of Sage Profiles From The Chl Cellmentioning
confidence: 99%